Trabajos de Grado - Osorio Rivera, Marinella; Restrepo Piedrahita , Daniela; Pérez Castaño, Ana Milagros; Arango Restrepo, Sara; Hoyos Vélez, Joan Sebastián; Álvarez Sánchez , Karen Lorena; Arias Rojas, Kelly Johana; Montoya Quintero , Estefanía (Pensar Historia, 2024)
.